The role of psychological flexibility and inflexibility in substance addiction, abuse, or misuse: a systematic review and meta‑analysis - Barrado-Moreno, Victoria; Serrano-Ibáñez, Elena Rocío; Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; Sánchez‑Meca, Julio (Springer Nature, 2025)
Psychological inflexibility (PI) and psychological flexibility (PF) are transdiagnostic mechanisms involved in the development, maintenance and treatment of SUDs. Evidence on the relationship between their components and substance abuse has not been investigated using a meta-analytic approach. The aim of this meta-analysis was to quantify the association between the dimensions of PF and PI, and substance abuse. A systematic literature review was conducted in four databases. A total of 24 studies were included. The associations were quantified using Pearson’s r correlation coefficients, and two separate meta-analyses were conducted: one for the association between mindfulness and substance abuse, and one for the association between experiential avoidance and substance abuse. The meta-analyses showed a low and negative mindfulness-substance abuse relationship (r = -0.25), and a moderate and positive experiential avoidance-substance abuse relationship (r = 0.34). One study reported a correlation of r = -0.17 between defusion and substance abuse. The search for studies on the remaining components was unsuccessful. Substance type and target population moderated the relationship between mindfulness and substance abuse. Clinical and empirical implications of these results are discussed, and recommendations and future research directions are outlined.
Keywords: Adaptación (Psicología); Abuso de sustancias - Aspectos psicológicos; Adicción - Aspectos psicológicos; Psychological flexibility; Psychological inflexibility; SUDs; Substance abuse; Substance misuse; Meta-analysis